Variants in the pancreatic CUB and zona pellucida-like domains 1 (CUZD1) gene in early-onset chronic pancreatitis: a possible new susceptibility gene - Rygiel, Agnieszka; Unger, Lara Sophie; Sörgel, Franziska Lena; Masson, Emmanuelle; Matsumoto, Ryotaro; Ewers, Maren; Chen, Jian-Min; Bugert, Peter; Buscail, Louis; Gambin, Tomasz; Oracz, Grzegorz; Winiewska-Szajewska, Maria; et al. (Pancreatology, 2022)
OBJECTIVE: Non-alcoholic chronic pancreatitis (NACP) frequently develops in the setting of genetic susceptibility associated with alterations in genes that are highly expressed in the pancreas. However, the genetic basis of NACP remains unresolved in a significant number of patients warranting a search for further risk genes. - DESIGN: We analyzed CUZD1, which encodes the CUB and zona pellucida-like domains 1 protein that is found in high levels in pancreatic acinar cells. We sequenced the coding region in 1163 European patients and 2018 European controls. In addition, we analyzed 297 patients and 1070 controls from Japan. We analyzed secretion of wild-type and mutant CUZD1 from transfected cells using Western blotting. - RESULTS: In the European cohort, we detected 30 non-synonymous variants. Using different prediction tools (SIFT, CADD, PROVEAN, PredictSNP) or the combination of these tools, we found accumulation of predicted deleterious variants in patients (p-value range 0.002-0.013; OR range 3.1-5.2). No association was found in the Japanese cohort, in which 13 non-synonymous variants were detected. Functional studies revealed >50% reduced secretion of 7 variants, however, these variants were not significantly enriched in European CP patients. - CONCLUSION: Our data indicate that CUZD1 might be a novel susceptibility gene for NACP. How these variants predispose to pancreatitis remains to be elucidated.
Gesehen am 26.08.2022